TINJAUAN ATAS PROSEDUR AUDIT PADA AKUNPIUTANG USAHA PT TVC OLEH KANTOR AKUNTANPUBLIK PAUL HADIWINATA, HIDAJAT, ARSONO, RETNO,PALILINGAN, & REKAN - Tania Vani Chulsum (2023)
Audit is a series of examination processes on financial statements by collecting and evaluating evidence that has been obtained related to information used as a reference material to assess the fairness of financial statements. Accounts receivable include accounts with high liquidity other than cash accounts, so the existence of these accounts is very influential on company performance, because it is quite crucial. In order to avoid the risk of misstatement and determine the fairness of the accounts receivable balance report, it is necessary to be examined by an independent auditor from the Public Accounting Firm. The purpose of writing this Final Project is to find out the review carried out on PT TVC's accounts receivable audit procedures. The procedures applied by KAP PKF Hadiwinata when carrying out the audit process on all accounts of PT TVC's financial statements, one of which is the accounts receivable account, can be concluded that PT TVC's accounts receivable have been presented fairly and no material misstatements have been found, because the contents of the report are in accordance with the applicable PSAK and SA.